A configuração de novos locais e práticas pedagógicas na escola: o museu escolar, os laboratórios e gabinetes de ensino do Colégio Marista Arquidiocesano de São Paulo (1908-1940) - Bocchi, Luna Abrano (2013)
This research aims to investigate the configuration of suitable places for teaching science in the early twentieth century, more specifically, how this process occurred at Colégio Marista Arquidiocesano de São Paulo, between the years 1908 and 1940. Both elementary and middle-school levels were analyzed and it was acknowledged that they had very different trajectories. However, these segments had in common the concern with the development of the senses of both children and young adults. In middleschool level the main concern can be related to science education and practical proposals. On the other hand, the elementary school was based on intuitive teaching. The observation, practical work and experimentation have been included among the dally activities of the school and should take place in appropriate locations, where it would be possible to keep teaching materials, as well as to propose practical situations with students. In this context, there were the establishment of school museums, cabinets and laboratories inside the school. These development were not only an indication that Colégio Marista Arquidiocesano de São Paulo followed the government guidelines but also the proof that they were a symbol of modern pedagogy. It could also be considered as advertising for the school